Analysis of Multicultural Education Values in the Book of Islamic Education and Character in Class VIII of Junior High School - Munauwarah, Rahmadin; Fathiha, Nuril (YASIN, 2022)
The research is motivated by the existence of such complex diversity in Indonesia. At one time, this diversity could potentially conflict with one another. Therefore, to avoid conflict, every citizen, especially Muslims, needs to be educated from an early age by applying multicultural values through education. One way is to include, internalize and integrate the values of multicultural education in Islamic Religious Education and Moral Education subject books. This study aims to find out whether or not there is a content of multicultural education values in Islamic Religious Education and Moral Education textbooks for class VIII SMP as well as the advantages and disadvantages in the book from the perspective of multicultural education.This type of research is library research. This research is descriptive-analytic in nature and equipped with complementary data. The method used is documentation, then analyzed using content analysis, reduction and interpretation methods. The results of this study indicate that; first, Islamic Religious Education and Character Education textbooks for class VIII SMP have all the values of multicultural education, namely the values of tolerance, equality, justice, and democracy. Second, the advantages of the book according to the perspective of multicultural education are that it contains values of multicultural education consisting of values of tolerance, equality, justice and democracy. In addition, there are three chapters that cover almost all the values of multicultural education, namely chapters IV, XI and chapter XIII. Meanwhile, the weakness is that there are still many chapters that do not contain the values of multicultural education, and the integration and internalization of Islamic teaching values with multicultural education in the book is still lacking and uneven. Then criticism of the misunderstanding of the meaning of the words and objectives contained in the book.